Design and Performance Analysis of an Innovative Flow Door in a Brick-Based Dual-Bin Compost Mixing System - Gusmiatun; Herlianto sapsidi Herli; supli effendi rahim (Journal of Smart Agriculture and Environmental Technology, 2025)
Compost production in Indonesia is often hampered by conventional methods that rely on manual mixing, resulting in lengthy processing times, high labor requirements, and inconsistent compost quality. This study aimed to develop a mechanical compost mixer system featuring an innovative flow gate in a dual-brick-bin setup. The innovation is designed to improve mixing efficiency, mixture homogeneity, and energy consumption. The research was conducted in Tanjung Tebal Village, Lahat Regency, from March to June 2024, using materials such as household organic waste, animal manure, coffee husks, dry leaves, fresh leaves, and the EM4 bioactivator. The methodology investigated using a comparison of a 9HP gasoline engine and equipped with the innovative flow gate to manual methods. Parameters compared include mixing time, energy consumption, homogeneity distribution, and residual material. The results show the mechanical system reduced mixing time by up to 30% from an average of 45 minutes using manual methods to 30 minutes, mixture homogeneity increased to 95% compared to 70% with manual methods, while residual material decreased from 15% to 6%. The flow gate innovation in the dual-brick-bin system proved effective in enhancing the efficiency of the compost mixing process. Implementation of this technology has the potential to support organic waste management in rural areas, reduce environmental pollution, and promote sustainable agriculture. Further research is recommended to evaluate the system’s efficiency on a larger scale.